The Deadly Facets of Terrorism. Issue 4 (24th July 2019) - Python, Andre; Illian, Janine B.; Jones-Todd, Charlotte M.; Blangiardo, Marta
Abstract: Can Bayesian models reveal the underlying processes that drive the lethality of non-state terrorism at a local level? Andre Python, Janine B. Illian, Charlotte M. Jones-Todd and Marta Blangiardo investigate